INTRODUCING BIOLOGY THROUGH COMICS: BIBLIOMETRIC ANALYSIS MAPPING - Abrori, Fadhlan Muchlas; Fadhail, Maulana Ahsan (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2025)
Using comics with biological content is an art method that is gaining popularity, but it is still uncommon. In contrast, the advancement of biology comics research is still infrequently reviewed by researchers. Based on this, this paper evaluated biology comics research using bibliometric analysis based on the Scopus database. We coded using numerous criteria, including documents and citations, as well as the dimensions of biology comics based on three timeline groupings (2011-2014, 2015-2018, 2019-2022). Based on documents and citations, we grouped them by top journals, top authors, and keywords that were mentioned the most by authors. Based on the dimensions of biology comics research, we examine research methodologies, research samples, biology topics, comics type, comics implementation, and comics roles. In the last part, we reflected on and described potential future research directions based on the collected information.